(untitled) (Libellarium: journal for research in the field of information and related sciences, 2022)
Purpose. The aim of this paper is to present one of the ways to protect and preserve cultural heritage in post-crisis situations. The paper presents the initiative of the European Solidarity Corps and its volunteer activities in Norcia with an emphasis on interventions and actions of fixing and preventing further deterioration of the Basilica of St. Benedict in Norcia after the 2016 earthquake. Approach/methodology. Research on the activities of the European Solidarity Corps initiative and its volunteer activities in Norcia was conducted by analysing archival material and literature. The paper refers to official documents of the Ministry of Culture in Italy, the European Commission and recent Italian papers on the subject. Findings. The first part of the paper presents the basic information and goals of the European Solidarity Corps initiative. The second part of the paper presents the state of the Basilica of St. Benedict in Norcia before the 2016 earthquake and the state of the Basilica during the earthquake. The main part of the paper presents the volunteer activities carried out by the European Solidarity Corps in ruined Norcia. The paper presents the work of student volunteers within the framework of the activities of the European Solidarity Corps at the Basilica of St. Benedict in Norcia. The fourth part of the paper points to the existence of an initiative in Croatia called Europske Snage Solidarnosti, which invites young professionals to participate in volunteer activities. Originality/value. The paper provides information about the existence of the European Solidarity Corps initiative. The successfully used EU funds for the post-earthquake reconstruction of the Basilica of St. Benedict in Norcia are pointed out. Information on the existence of the European Solidarity Corps and their potential use in similar situations in Croatia is important. The paper can inform and encourage readers to join the European Solidarity Corps and participate in their volunteer projects, or to volunteer for another organization or institution.